SKIMMING AND SCANNING TECHNIQUE: IS IT EFFECTIVE FOR IMPROVING INDONESIAN STUDENTS’ READING COMPREHENSION? - Aditya Ridho Fatmawan; Ni Putu Artila Dewi; I Putu Agus Dharma Hita (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Skimming and scanning are reading techniques that involve quick eye movements and the use of keywords to swiftly navigate through text, each serving slightly different purposes. Skimming entails reading rapidly to obtain a general overview of the material, whereas scanning involves reading rapidly to locate specific facts. In essence, skimming provides readers with a sense of the overall information contained in a section, while scanning assists readers in pinpointing particular details. This study conducted a comprehensive review of existing literature using a systematic approach. The systematic literature review (SLR) method entails a structured process of gathering, evaluating, and analyzing pertinent information from diverse sources, followed by synthesizing the findings to draw conclusions. The findings revealed that skimming and scanning are seemingly straightforward reading strategies. Employing skimming and scanning strategies proves effective in enhancing students' comprehension in reading tasks. In the scope of Indonesian students, it was found that the skimming and scanning give positive effect toward students’ reading comprehension, especially in speed reading and reading improvement. In conclusion, skimming and scanning strategies are efficient in reducing time consumption during reading tasks.